EDUKASI LITERASI KEUANGAN BAGI ANAK PANTI ASUHAN GAMALIEL - Riadi Riadi; Tina Novianti Sitanggang; Jhon Lismart Benget. P; Ronald Hasudungan Rajagukguk (Jurnal Pengabdian Bukit Pengharapan, 2026)
The ability of individuals in each generation to understand and apply their potential and skills in information management, including financial management, aims to ensure the future and avoid financial problems for Generation Alpha. To equip the children at the Gamaliel Orphanage to plan their future, starting with providing information and knowledge in the form of financial literacy to broaden their understanding of finance and banking, by encouraging early savings, is the goal of this service by providing counseling.